Case report: A rare case of synchronous mucinous neoplasms of the renal pelvis and the appendix - Zou, Yuhua; Xie, Xiaojuan; Wang, Qinlin; Zhong, Cunzhi; Liu, Quanliang (Frontiers in Oncology, 2023)
Background: Mucinous neoplasms are tumors arising in the epithelial tissue, characterized by excessive mucin secretion. They mainly emerge in the digestive system and rarely in the urinary system. They also seldom develop in the renal pelvis and the appendix asynchronously or simultaneously. The concurrence of this disease in these two regions has not yet been reported. In this case report, we discuss the diagnosis and treatment of synchronous mucinous neoplasms of the right renal pelvis and the appendix. The mucinous neoplasm of the renal pelvis was preoperatively misdiagnosed as pyonephrosis caused by renal stones, and the patient underwent laparoscopic nephrectomy. Herein, we summarize our experience with this rare case in combination with related literature. Case presentation: In this case, A 64‐year‐old female was admitted to our hospital with persistent pain in the right lower back for over a year. Computer tomography urography (CTU) showed that the patient was confirmed as right kidney stone with large hydronephrosis or pyonephrosis, and appendiceal mucinous neoplasm (AMN). Subsequently, the patient was transferred to the gastrointestinal surgery department. Simultaneously, electronic colonoscopy with biopsy suggested AMN. Open appendectomy plus abdominal exploration was performed after obtaining informed consent. Postoperative pathology indicated low-grade AMN (LAMN) and the incisal margin of the appendix was negative. The patient was re‐admitted to the urology department, and underwent laparoscopic right nephrectomy because she was misdiagnosed with calculi and pyonephrosis of the right kidney according to the indistinctive clinical symptoms, standard examination of the gelatinous material, and imaging findings. Postoperative pathology suggested a high‐grade mucinous neoplasm of the renal pelvis and mucin residing partly in the interstitium of the cyst walls. Good follow-up results were obtained for 14 months. Conclusion: Synchronous mucinous neoplasms of the renal pelvis and the appendix are indeed uncommon and have not yet been reported. Primary renal mucinous adenocarcinoma is very rare, metastasis from other organs should be first considered, especially in patients with long-term chronic inflammation, hydronephrosis, pyonephrosis, and renal stones, otherwise, misdiagnosis and treatment delay may occur. Hence, for patients with rare diseases, strict adherence to treatment principles and close follow‐up are necessary to achieve favorable outcomes.